Developing a mastery - humility convergence model for a tauhidic - based engineering curriculum - Ruslan Hassan (Kulliyyah of Education, International Islamicc University Malaysia, 2021)
This thesis addresses the void in the spiritual dimension in the Madinah Accord meant for substantial equivalence of accreditation to recognise undergraduate engineering qualifications in Muslim countries. The Cartesian dualism exists in the curriculum despite its name perpetuating a disconnect between the Creator and the created. For realignment, the doctrine of Tawhid is regained and intellectually reconstructed utilising Bil-Mizan (balance) concept to be comprehended and translated into actions by the present generation. The research adopted the Mixed-Methods Exploratory Sequential Design Approach utilising interviews and document analyses followed by questionnaire survey involving academics and students of two local universities. The enquiry was driven by the Straussian grounded theory to reach the theoretical saturation point. The research questions addressed mastery, humility and their convergence. Before the primary interviews, piloted interviews and survey were performed. The main interviews then documented 30 transcripts and uploaded as open, axial and selective codes using NVivo. Six constructs with 24 items were developed for the main questionnaire survey receiving 507 responses. Using SPSS Amos, the construct validity achieved CFI .963≥.95, TLI .956≥.90 and RMSEA .068≤.08. Upon verifying the measurement model, SEM then confirmed the theoretical proposition (HC), that mastery and humility formed the converging variable. The second hypothesis (HM) relating mastery with IDP was significant, but the third hypothesis (HH) relating teaching modules with humility was insignificant. In conclusion, the theory is grounded in the data. The convergence occurs when all things are at their correct positions. This condition, achieved by wisdom manifested by ‘adab’ (proper conduct), is defined as justice thus assuring stability. Allah (SWT) as Al-‘Adl (Justice) and Al-Khalik (Creator) governs this condition. An engineer with ‘adab’ as an ‘abd’ (servant) and Khalifah (vicegerent) on earth can become closer to Him through his engineering design. A Murabbi academic can incorporate both of His names in statics as in reinforced beam and dynamics in colloids settling.